Childhood maltreatment, moral disengagement, and adolescents' cyberbullying perpetration: Fathers' and mothers' moral disengagement as moderators. (June 2019) - Wang, Xingchao; Yang, Jiping; Wang, Pengcheng; Lei, Li
Abstract: Fathers' moral disengagement and mothers' moral disengagement were examined as the two moderators of the adverse effect of childhood maltreatment on adolescents' moral disengagement and cyberbullying perpetration. Participants were 412 Chinese adolescents ( M age  = 13.53 years, SD  = 0.91) and their fathers and mothers. Results indicated that adolescents with high childhood maltreatment were more likely to cyberbully others, and this relation was mediated by adolescents' moral disengagement. Furthermore, fathers' moral disengagement moderated the relation between childhood maltreatment and adolescents' moral disengagement only, but not the relation between childhood maltreatment and cyberbullying perpetration. Mothers' moral disengagement moderated the relation between childhood maltreatment and cyberbullying perpetration only, but not the relation between childhood maltreatment and adolescents' moral disengagement. Highlights: Adolescents with high childhood maltreatment were more likely to cyberbully others. This relation was mediated by adolescents' moral disengagement. Fathers' moral disengagement moderated the relation between childhood maltreatment and adolescents' moral disengagement. Mothers' moral disengagement moderated the relation between childhood maltreatment and cyberbullying perpetration.